2010
DOI: 10.1111/j.1551-2916.2010.03608.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Densification of Monolithic Zirconium Carbide by Reactive Hot Pressing

Abstract: Synthesis and densification of monolithic zirconium carbide (ZrC) has been carried out by reactive hot pressing of zirconium (Zr) and graphite (C) powders in the molar ratios 1:1, 1.25:1, 1.5:1, and 2:1 at 40 MPa, 12001-16001C. Monolithic ZrC could be synthesized with a C/Zr ratio B0.5-1.0 and the post heat-treated samples have the lattice parameter in the range 4.665 to 4.698 Å . Densification improves with an increasing deviation from the stoichiometry. Fine-grained (B1 lm) and nearly fully dense material (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
40
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 23 publications
8
40
3
Order By: Relevance
“…21,22 In particular, it was shown that as 'x' decreased from 1 to 0.67, the necessary process temperature reduced from 1600 to 1200 • C. The present work seeks to deter- * Corresponding author. Tel.…”
Section: Introductionmentioning
confidence: 97%
“…21,22 In particular, it was shown that as 'x' decreased from 1 to 0.67, the necessary process temperature reduced from 1600 to 1200 • C. The present work seeks to deter- * Corresponding author. Tel.…”
Section: Introductionmentioning
confidence: 97%
“…8 In addition to the additive approach that is commonly used to produce dense ZrC-based ceramics, reactive hot pressing (RHP) is another way to obtain high-dense ceramics, which has an advantage of producing ceramics at reduced temperatures compared with non-reactive processes, 15,16 Nachiappan et al carried out the synthesis and densification of ZrC by RHP of Zr and C powders. 17 The results showed that nearly fully dense material with fine grains could be prepared at temperature as low as 1200 • C with C/Zr ∼0.67.…”
Section: Introductionmentioning
confidence: 97%
“…With the high-speed development of the new technology in the field of aviation and space industries, powder metallurgy and atomic energy, the advanced ultra-high temperature structure materials (such as the borides, carbides of the refractory metals zirconium, hafnium and tantalum) have attracted more and more attention due to the outstanding physical and chemical properties [1][2][3] . And zirconium carbide is one representative of these ultra-high temperature structure materials.…”
Section: Introductionmentioning
confidence: 99%